Pola Asuh Anak Yatim Di Panti Asuhan Muhammadiyah Putri Pare - Ratna Sa’idah (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2015)
Family is a smallest social unit. The change number of the family member will influence the atmosphere of theÂ family relationship which influence feeling, thought, and attitude of the members. The fatherâ€™s dead whichÂ makes children become orphan is a fact of life. It always makes family atmosphere become sad, and it causesÂ bad situation for the children in which they lose love and good leader. Therefore, it is important to develop theirÂ potentials which will give benefits for their life and their family.Â Developing orphansâ€™ positive potentials can be done at home or in orphanage. This article aims at investigatingÂ orphans parenting in Muhammadiyah girl orphanage in Pare. The result shows that the orphans parentingÂ in Muhammadiyah girl orphanage in Pare can be seen from the parenthood which has good attitude andÂ character. She has motherly attitude, patient, discipline, and perceptive with the orphansâ€™ condition. TheÂ learning activity in the orphanage is 24 hours. The orphans learn religious knowledge, foreign language, andÂ entrepreneurship. The parenting model used are that the parenthood educate the orphans as like her ownÂ children, and the relationship between the old and the young orphans is like own brother-sister. The supportingÂ factors of the parenting in this orphanage are honest intention, community support, financial source, andÂ facilities. Meanwhile, the problems faced are juvenile delinquency and insufficient facilities.